Phenotypic diversity in Bronze Age pigs from the Alpine and Central Plateau regions of Switzerland. (October 2018) - Bopp-Ito, Miki; Cucchi, Thomas; Evin, Allowen; Stopp, Barbara; Schibler, Jörg
Abstract: Pig husbandry was one of the key components of Swiss Bronze Age communities. However, the extent of diversity within husbandry practices across these communities remains unclear, particularly for the Alpine and Swiss Central Plateau regions. Differences in tooth size and shape provide valuable proxies for exploring the history of pig populations and inferring changes to cultural and socio-economic behaviours. Thus, to explore geographical and chronological changes in pig husbandry in Bronze Age Switzerland, we tracked the phenotypic diversification of pig populations using the geometric morphometrics of the second and third lower molars as proxies. Our results confirmed the phenotypic homogeneity of Alpine pig populations during the Bronze Age, both in size and shape. Thus, strong homogeneity appeared to exist in the genetic make-up of pig herds in this area, which can probably be attributed to interactions among the local communities. Conversely, pig populations from the Swiss Central Plateau exhibited a greater diversification in shape between the eastern and western populations, indicating a lack of genetic interaction. In parallel, we observed a significant decline in the size of the east Central Plateau pig population during the Late Bronze Age, possibly due to shifts in husbandry practices induced by changes in forest management. Based on our findings, we hypothesise that geographical, topographical, environmental, and cultural factors influenced local pig husbandry practices and the phenotypic diversity of pig molars between regions in Bronze Age Switzerland. However, further investigations comparing Bronze Age pig populations over a broader scale are required, using genetic and isotopic markers to further test changes in husbandry practices and the genetic diversity. Highlights: We assessed Bronze Age pig tooth size and shape using geometric morphometrics. The Alpine pig populations showed phenotypic homogeneity in size and shape. The Central Plateau pig populations exhibited a greater phenotypic diversity. The East Central Plateau pigs experienced a significant tooth size reduction. There was a greater difference in shape between the three regional Bronze Age pigs.